Economic Growth and Development in Malaysia : Policy Making and Leadership - Aznam Yusof, Zainal; Bhattasali, Deepak (World Bank, Washington, DC, 2017)
Malaysia is a multiethnic, upper-middle-income country that has relied heavily on income from its natural resources to engineer successful diversification into manufacturing and sharply increased incomes for all ethnic groups. This paper examines the role of the policy-making process and national leadership in effecting this structural change and growth with equity. It discusses the government's role in transforming corporate ownership patterns while nurturing industrial enterprises into niche products within complex value-added chains. At the same time, the paper underscores the difficulties and costs of attempting to move into areas where an economy has no strong advantages, in this case heavy industries. Privatization is seen to have been a powerful tool for expanding private enterprise despite limited entrepreneurial skills, but it is questionable as a sustainable strategy; the aggressive formation of new firms seems to offer better long-term prospects. An appropriate regime of policy making and implementation is required, characterized by political determination, stability, high attention to growth with equity, experimentation, and an ability to learn through implementation, both at home and from the experience of others. These are key factors accounting for the relative success of Malaysia. Nothing in the Malaysian experience suggests that it is possible or desirable to undertake reforms serially; in fact, the evidence suggests that the "reform cluster" approach to policy implementation is more effective because it addresses several coordination problems at the same time.